Study on stress distribution of a subsea Ram BOP body based on simulation and experiment. (April 2015) - Tang, Y.; Liu, Q.Y.; Xie, C.; Chen, S.W.
Highlights: FEA method and STE method are used to study on stress distribution of Ram BOP body. The results of the FEA method are essentially consistent with the STE method. The stress concentration areas of the body of the double Ram BOP were analyzed. This study will provide references for related research of the body of the Ram BOP. Abstract: Taking a double ram blowout preventer (Ram BOP) 2FZ54-105 as an example, we have analyzed the stress distribution rule and the stress concentration regions of its body under the rated working conditions (RWC) and the hydrostatic test pressure (HTP) with the finite element analysis (FEA) methods and the stress testing experiment (STE) methods. And then it was found that the simulation results of the FEA were essentially consistent with the STEs through the comparative analysis, and the feasibility and accuracy of these two methods are corroborated each other. Moreover, we confirm that the body strength meets the design requirements and using conditions by combining with the analysis results of two methods. Finally, the stress concentration regions of inner and outer surfaces of the body were summarized and gained based on the comprehensive analysis of all cases. These methods and results in this study can provide references for structure modified design of the body and guide on-site maintenance and safety evaluation of the Ram BOP in service.